CRBN Is a Negative Regulator of Bactericidal Activity and Autophagy Activation Through Inhibiting the Ubiquitination of ECSIT and BECN1 - Kim, Mi-Jeong; Min, Yoon; Shim, Jae-Hyuck; Chun, Eunyoung; Lee, Ki-Young (Frontiers in Immunology, 2019)
Cereblon (CRBN) as a multifunctional protein has been extensively studied. Here, we show that CRBN is a negative regulator of bactericidal activity and autophagy activation. Mitochondrial localization of CRBN was significantly increased in response to Toll-like receptor 4 (TLR4) stimulation. CRBN interrupted the association of evolutionarily conserved signaling intermediate in Toll pathways (ECSIT)-TNF-receptor associated factor 6 (TRAF6) complex, thereby inhibiting the ubiquitination of ECSIT, which plays a pivotal role for the production of mitochondrial reactive oxygen species (mROS). Subsequently, mROS levels were markedly elevated in CRBN-knockdown (CRBNKD) THP-1 cells, and that led to resistance against S. typhimurium infection, indicating CRBN is a negative regulator of bactericidal activity through the regulation of mROS. Additionally, CRBN inhibited TRAF6-induced ubiquitination of BECN1 (Beclin 1), and that induced autophagy activation in CRBNKD THP-1, CRBN-knockout (CRBNKO) H1299, and CRBNKO MCF7 cancer cells in response to TLR4 stimulation. Notably, we found that the ability of cancer migration and invasion was significantly enhanced in CRBNKO H1299 and CRBNKO MCF7 cancer cells, as compared with those of control cancer cells. Collectively, these results suggest that CRBN is a negative regulator of bactericidal activity and autophagy activation through inhibiting the TRAF6-induced ubiquitination of ECSIT and BECN1, respectively.